Necessity Entrepreneurship and Competitive Strategy - Jörn Hendrich Block; Karsten Kohn; Danny Miller; Katrin Ullrich (Institute for the Study of Labor (IZA), 2014)
Many start-ups chose to compete with incumbent firms using one of two generic strategies: cost leadership or differentiation. Our study demonstrates how this choice depends on whether the startup was founded out of necessity. Our results, based on a representative data set of 4,568 German start-ups, show that necessity entrepreneurs are more likely than other entrepreneurs to pursue a cost leadership strategy, and less likely to pursue a differentiation strategy. Decomposition analyses further show that up to half of the difference in choice of strategy can be attributed to distinct endowments of human capital, socio-economic attributes, and start-up project characteristics that correlate with necessity entrepreneurship.
Keywords: L10; L26; 330; cost leadership; competitive strategy; new venture strategy; necessity entrepreneurship; product differentiation; decomposition analysis